Metabolite profiling and inhibitory properties of leaf extracts of Ficus benjamina towards α-glucosidase and α-amylase. Issue 1 (1st January 2018) - Mumtaz, Muhammad Waseem; Al-Zuaidy, Mizher Hezam; Abdul Hamid, Azizah; Danish, Muhammad; Akhtar, Muhammad Tayyab; Mukhtar, Hamid
ABSTRACT: The use of antioxidant-rich medicinal plants having the potential to reduce oxidative stress and postprandial hyperglycemic pressure is one of the most promising option for the management of diabetes. This study presents information on metabolite profiling and in vitro anti-diabetic effects of leaf extracts of Ficus benjamina . The DPPH (2, 2-diphenyl-1-picrylhydrazyl radicals) assay was performed to determine the in vitro antioxidant potential of the plant extracts. The anti-diabetic effects were investigated by evaluating inhibitory properties of F. benjamina leaf extracts towards carbohydrate hydrolyzing enzymes, i.e., α-glucosidase and α-amylase, whereas 1 H NMR and UHPLC-QTOF-MS/MS analytical methods were employed for metabolite profiling of F. benjamina leaf extracts. Among 40, 60, 80, and 100% ethanolic leaf extracts of F. benjamina, 80% ethanolic extract exhibited the highest antioxidant activity based upon its DPPH radical scavenging ability (IC50 value: 63.71 ± 2.66 µg/mL). The 80% ethanolic leaf extract of F. benjamina also proved to be the most efficient α-glucosidase and α-amylase inhibitor with IC50 values of 9.65 ± 1.04 µg/mL and 13.08 ± 1.06 µg/mL, respectively; these values were even better than acarbose with α-glucosidase inhibition activity (IC50 = 116.01 ± 3.83 µg/mL) and α-amylase inhibition activity (IC50 = 152.66 ± 7.32 µg/mL). Moreover, a total of 31 metabolites were identified in F. benjamina leaf extract, which may have the potential to contribute to its antioxidant and inhibitory properties against carbohydrate hydrolyzing enzymes. The findings of this study depict F. benjamina leaf extracts as a promising α-glucosidase and α-amylase inhibitor, and therefore, can be utilized for the development of anti-diabetic functional diets/nutra-pharmaceuticals.